The First Documented Forensic Entomology Case in Thailand - Sukontason K. (2014)
The forensic entomology case described herein is the first such cast documented in Thailand. A mummified corpse of a 32-yr-old man was discovered in a forested habitat, with the larvae of six species of flies (Diptera) found in association with the corpse at the time of its discovert, i.e., those of Hydrotaea (=Ophyra) spinigera Stein (family Muscidae), Piophila casei (L.) (family Piophilidae). Megaselia scalaris (Loew) (family Phoridae), Sargus sp. (family Stratiomyidae), and larvae of two unidentified flesh fly species (family Sarcophagidae). The presence and age of the larval specimens of P. casei, M. scalaris, and H. spinigera gave entomological evidence that the postmortem interval for the corpse was 3-6 mo. This report also documents some of the forensically important fly species that occur in Thailand.